An Analysis of Translation Shift in Novel Shine by Jessica Jung and Its Translation - Nita Wardatul Latifah; Baharuddin Baharuddin; Udin Udin (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
The purpose of this study is to analyze the translation shift and translation quality of novel shine. The objectives of this research are to (1) classify and describe types of level shifts in novel Shine, and (2) determine which type of level shift has the highest level of translation quality. The instrument used in this study is an indicator of translation quality which consists of indicators of accuracy, acceptability, and readability. This research employs both quantitative and qualitative methods. The data are collected through documentation and analyzed using comparative techniques. The researcher revealed that there are 18 cases of level shift found in novel Shine, with 11 cases of case shift and 7 cases of aspect shift. Based on the result of the calculation, it was found that case shift received 99% score of translation quality consisting 31 (100%) scores of accuracy, 30 (97%) scores of acceptability, and 31 (100%) scores of readability. Meanwhile, aspect shift received 97% scores of translation quality, consisting 19 (90%) scores of accuracy, 21 (100%) scores of acceptability, and 21 (100%) scores of readability. From the result of the calculation above it can be concluded that case shift received the highest score of translation quality.Keywords: level shift, translation quality, novel